Impairment-Based Rehabilitation With Patterned Electrical Neuromuscular Stimulation and Lower Extremity Function in Individuals With Patellofemoral Pain: A Preliminary Study - Glaviano, Neal R. (J Athl Train, 2019)
CONTEXT: Patellofemoral pain (PFP) is a chronic condition that presents with lower extremity muscle weakness, decreased flexibility, subjective functional limitations, pain, and decreased physical activity. Patterned electrical neuromuscular stimulation (PENS) has been shown to affect muscle activation and pain after a single treatment, but its use has not been studied in a rehabilitation trial. OBJECTIVE: To determine the effects of a 4-week impairment-based rehabilitation program using PENS on subjective function, pain, strength, range of motion, and physical activity in individuals with PFP. DESIGN: Randomized controlled trial. SETTING: Laboratory. PATIENTS OR OTHER PARTICIPANTS: A total of 21 patients with PFP (5 males, 16 females; age = 23.4 ± 7.6 years, height = 168.0 ± 7.5 cm, mass = 69.0 ± 19.5 kg). INTERVENTION(S): Participants completed a 4-week supervised rehabilitation program in conjunction with random assignment to receive PENS or sham treatments. MAIN OUTCOME MEASURE(S): Subjective function, pain, strength, range of motion, and physical activity levels were assessed prerehabilitation and postrehabilitation. Subjective function and pain were also assessed at 6 and 12 months postrehabilitation. Repeated-measures analyses of variance and Tukey post hoc testing were conducted with α ≤ .05. We calculated Cohen d effect sizes with 95% confidence intervals. RESULTS: Both groups had statistically and clinically meaningful differences in subjective function, pain, strength, range of motion, and activity level after 4 weeks of impairment-based rehabilitation. Improved subjective function was observed in both groups at 6 and 12 months after the interventions. The PENS group had improvements in current pain for all 3 postrehabilitation times compared with baseline measures. CONCLUSIONS: An impairment-based intervention effectively improved subjective function, pain, strength, range of motion, and physical activity levels in individuals with PFP. Participants who received PENS in addition to the rehabilitation program had improved current pain at 6 and 12 months postrehabilitation compared with baseline scores. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT02441712